Making BaZrS3 Chalcogenide Perovskite Thin Films by Molecular Beam Epitaxy. (16th August 2021) - Sadeghi, Ida; Ye, Kevin; Xu, Michael; Li, Yifei; LeBeau, James M.; Jaramillo, Rafael
Abstract: The making of BaZrS3 thin films by molecular beam epitaxy (MBE) is demonstrated. BaZrS3 forms in the orthorhombic distorted‐perovskite structure with corner‐sharing ZrS6 octahedra. The single‐step MBE process results in films smooth on the atomic scale, with near‐perfect BaZrS3 stoichiometry and an atomically sharp interface with the LaAlO3 substrate. The films grow epitaxially via two competing growth modes: buffered epitaxy, with a self‐assembled interface layer that relieves the epitaxial strain, and direct epitaxy, with rotated‐cube‐on‐cube growth that accommodates the large lattice constant mismatch between the oxide and the sulfide perovskites. This work sets the stage for developing chalcogenide perovskites as a family of semiconductor alloys with properties that can be tuned with strain and composition in high‐quality epitaxial thin films, as has been long‐established for other systems including Si‐Ge, III‐Vs, and II‐VIs. The methods demonstrated here also represent a revival of gas‐source chalcogenide MBE. Abstract : BaZrS3 thin films are made by molecular beam epitaxy. The single‐step, gas‐source process results in films smooth on the atomic scale, with near‐perfect BaZrS3 stoichiometry and an atomically‐sharp interface with the LaAlO3 substrate. This work sets the stage for developing chalcogenide perovskites as semiconductors with properties that can be tuned with strain and composition in high‐quality epitaxial films.